Sex related differences in nonmotor symptoms of patients with idiopathic blepharospasm - Jing Yang (Nature Portfolio, 2021)
Abstract Idiopathic blepharospasm shows a female predominance in prevalence, whether there are sex-related differences in distributions of nonmotor symptoms (NMSs) and predictors of quality of life are unknown. Four hundred and twenty-five patients with idiopathic blepharospasm were consecutively recruited, and underwent assessments including dystonia severity, mood disturbances, sleep disturbances, cognition, ocular symptoms, and quality of life. Frequencies and distributions of NMSs, and predictors of quality of life in female and male patients were investigated. NMSs existed in majority of male (94.0%) and female (95.8%) patients. The frequencies of depression, cognition dysfunction, and poor sleep quality were higher in female patients, while the frequency of excessive daytime sleepiness was higher in male patients. More female (79.5%) patients had multiple NMS domains affected than male (70.1%) patients (p = 0.040). Quality of life was associated with depression, anxiety and motor severity for female patients (adjusted R2 = 0.367, p < 0.001), while associated with depression, excessive daytime sleepiness and motor severity for male patients (adjusted R2 = 0.430, p < 0.001). The highly prevalent coexistence of multiple NMSs found in patients with blepharospasm support that blepharospasm is a network disorder. The sex-related differences in the pattern of NMSs and predictors of quality of life may aid the development of tailored management of blepharospasm.